Distance Learning Courses become more popular in rural areas then urban areas? (International Journal of Scientific Research and Management (IJSRM), 2017)
Mukhopadhyay (1998) described distance education and differentiated it from open education as “Distance education is a mode of delivery and not an educational system; open education is a system – distance education is often the delivery mode of open education” This research addresses the roles of distance education in rural and undeveloped areas distance education is very useful. Distance education promotes and develops the right of every person to enjoy access to quality education. Distance students can save costs because people do not have to travel to campus to attend classes on regular scheduled basis, nor live on campus, although they will have to pay for tuition fees and expenses for the purchase of learning materials. This relatively much lower cost of distance education on the parts of the students compared to the face-to-face mode of education should improve participation and expand greater opportunities for those socially and economically less advantaged groups of the society, particularly women to have access to quality education higher education at affordable costs.